Determinação dos efeitos do meio e estimativa de herdabilidade do peso ao nascer em bovinos da raça Charolesa - Rocha, Marco Antônio da; Mizubuti, Ivone Yurika; Furiatti, Reginaldo (Semina: Ciências Agrárias, 1983)
Effects of environment and inheritance on weight at birth were studied in a herd located at the city of Bagé in Rio Grande do Sul, BRASIL. The size of the sample included a total of 131 animals and the mathematical model applied to the data included the following variables: year of birth, sire, sex and age of dam. Results showed that only the age of dam was signifcant (P < 0,05). Heritability was estimated through the method of correlation between paternal half sibs, and 0.30 Â± 0,19.